1996
DOI: 10.1084/jem.183.2.561
|View full text |Cite
|
Sign up to set email alerts
|

Clonal stability of blood cell lineages indicated by X-chromosomal transcriptional polymorphism.

Abstract: SummaryThe idea that stem cells oscillate between a state of activity and dormancy, thereby giving rise to differentiating progeny either randomly or in orderly clonal succession, has important implications for understanding normal hematopoiesis and blood cell dyscrasias. The degree of clonal stability in individuals also has practical implications for the evaluation of clonal lymphomyeloproliferative diseases. To evaluate the clonality pattern of the different types of blood cells as a function of time we hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
68
3

Year Published

1997
1997
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(76 citation statements)
references
References 30 publications
5
68
3
Order By: Relevance
“…First, several groups have demonstrated small differences in XCIPs from T cells and granulocytes in healthy subjects. 24,29,32,33 We show here that these differences result in wide confidence limits for the calculated proportion of V617F Ϫ cells that are apparently clonally derived. Importantly, this variability is systematically biased toward overestimating the proportion of clonally derived granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…First, several groups have demonstrated small differences in XCIPs from T cells and granulocytes in healthy subjects. 24,29,32,33 We show here that these differences result in wide confidence limits for the calculated proportion of V617F Ϫ cells that are apparently clonally derived. Importantly, this variability is systematically biased toward overestimating the proportion of clonally derived granulocytes.…”
Section: Discussionmentioning
confidence: 99%
“…This slow cycling behavior of baboon PHSCs is in agreement with the data generated by other researchers in other large animal models, including cats and rhesus macaques, and in humans. 13,19,[44][45][46][47][48] In particular, on the basis of measurements of telomere shortening in humans, Rufer et al 44 have previously reported that a rapid expansion of stem cells occurs early in life, followed by a marked decrease in the rate of stem cell divisions in the years that follow. They concluded that 15 to 30 stem cell divisions occur during the first half-year of life followed by less than 1 stem cell division per year in following years.…”
Section: Discussionmentioning
confidence: 99%
“…tional products (10,11). We have verified the reproducibility, sensitivity, and quantitative nature of rtPCR-LDR (10)(11)(12) This ASPCR assay is a modification of the previously reported ASPCR (13), PCR-ASOH (14) and PCR amplification of specific alleles (PASA) (15). The utility of PASA for this type of application is limited because the mismatched pairing which occurs at the 3 Ј end of the primer-template duplex (i.e., T:C, T:G, T:T) is amplified by Taq polymerase as efficiently as the perfectly complementary primer-template duplexes.…”
Section: Discussionmentioning
confidence: 96%
“…These assays are limited by racial specificity, lack of quantitation, and inapplicability to nonnucleated cells such as platelets and reticulocytes. We recently developed a clonality assay based on transcriptional polymorphisms of two ubiquitously expressed X chromosome genes; G6PD (C/T at 1311) and palmitoylated membrane protein, p55 (G/T at cDNA 358) (10,11,12). The assay uses reverse transcription polymerase chain reaction followed by ligase detection reaction (rtPCR-LDR) 1 (10,11,12) to distinguish the transcriptionally active X chromosome.…”
Section: Introductionmentioning
confidence: 99%